2023
DOI: 10.1017/s026646232300020x
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of information specialists and statisticians in systematic reviews

Abstract: Background Systematic reviews (SRs) are usually conducted by a highly specialized group of researchers. The routine involvement of methodological experts is a core methodological recommendation. The present commentary describes the qualifications required for information specialists and statisticians involved in SRs, as well as their tasks, the methodological challenges they face, and potential future areas of involvement. Tasks and qualifications Information specialists select the infor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…For example, Aamodt et al (2019) found that librarian co‐authored systematic reviews were associated with a lower risk of bias while Rethlefsen et al (2015) found that librarian co‐authors correlated with higher quality reported search strategies. Waffenschmidt and Bender (2023) argue that the inclusion of information specialists to select information sources, develop search strategies, conduct the searches, and report the results increases the trustworthiness of systematic reviews.…”
Section: Process Of Preparing Reviewsmentioning
confidence: 99%
“…For example, Aamodt et al (2019) found that librarian co‐authored systematic reviews were associated with a lower risk of bias while Rethlefsen et al (2015) found that librarian co‐authors correlated with higher quality reported search strategies. Waffenschmidt and Bender (2023) argue that the inclusion of information specialists to select information sources, develop search strategies, conduct the searches, and report the results increases the trustworthiness of systematic reviews.…”
Section: Process Of Preparing Reviewsmentioning
confidence: 99%